Nuclear and Chloroplast Sequences Resolve the Enigmatic Origin of the Concord Grape - Wen, Jun; Herron, Sterling A.; Yang, Xue; Liu, Bin-Bin; Zuo, Yun-Juan; Harris, AJ; Kalburgi, Yash; Johnson, Gabriel; Zimmer, Elizabeth A. (Frontiers in Plant Science, 2020)
Despite the commercial importance of the Concord grape, its origin has remained unresolved for over 150 years without a comprehensive phylogenetic analysis. In this study we aimed to reconstruct the evolutionary history of the Concord grape using sequence data from four nuclear markers (AT103, GAI1, PHYA, and SQD1), six plastid markers (matK, psbA-trnH, petN-trnC, ycf1, trnL-F, and trnS-G), and the plastid genome. We sampled extensively the Vitis species native to northeastern North America as well as representative species from Europe and Asia, including the commercially important Vitis vinifera (wine grape), a native European species with hermaphroditic flowers, and its wild progenitor, V. vinifera subsp. sylvestris. We also sequenced the plastid genome of one accession of the Concord grape and compared the plastid genome data to the recently published data set of Vitis plastomes. Phylogenetic analyses of the plastid and nuclear data using maximum likelihood and Bayesian inference support the hybrid origin of the Concord grape. The results clearly pinpoint the wine grape, V. vinifera, as the maternal donor and the fox grape, Vitis labrusca, which is common in northeastern North America, as the paternal donor. Moreover, we infer that the breeding history of the Concord grape must have involved the backcrossing of the F1 hybrid with the paternal parent V. labrusca. This backcrossing also explains the higher morphological similarity of the Concord grape to V. labrusca than to V. vinifera. This study provides concrete genetic evidence for the hybrid origin of a widespread Vitis cultivar and is, therefore, promising for similar future studies focused on resolving ambiguous origins of major crops or to create successful hybrid fruit crops.